Virtual meeting ground for colonial (re)interpretation of the Banda Islands, Indonesia - Donkersgoed, Joëlla van (UI Scholars Hub, 2019)
The history of the Banda Islands is revealed in material and immaterial heritage which can still be narrated, visited and experienced today. Using the technological tools available in the Digital Humanities, this paper proposes a project to create a virtual interactive platform in which documents and stories related to the colonial past can be gathered. Tools like crowd-sourcing and crowd-mapping can be used to establish this archive from the bottom-up, creating a platform allowing both the former colonizer and colonized to reflect on the past. Moreover, it will provide scholars with a source of information to revisit the history of the Banda Islands. This particular history is part of the current public debate in the Netherlands regarding the colonial past, moreover, it is central to the narrative concerning the ongoing conservation efforts to prepare the islands’ heritage to become an UNESCO World Heritage site for Indonesia.